Dirty Money on Holy Ground: Isolation of Potentially Pathogenic Bacteria and Fungi on Money Collected from Church Offerings - Akebe Luther King ABIA; Eunice UBOMBA-JASWA (Tehran University of Medical Sciences, 2019)
Background: Fomites (including money) can transmit diseases to humans. How the nature of money influences contamination has not been adequately demonstrated. Moreover, such studies in church settings are non-existent. Thus, we studied how money collected from a church could serve as human disease transmission vehicles. Methods: Overall, 284 money samples (currency notes and coins) were collected during two Sundays in the months of Nov and Dec 2015 from a church congregation in Pretoria, Gauteng, South Africa. The presence of potentially pathogenic bacteria and fungi were investigated using culture (Colilert® method) and molecular methods (Sanger sequencing). Scanning Electron Microscopy (SEM) was used to visualize the possible positions of the bacteria on various parts of a currency note. Results: Of the 192 samples (first sampling round), 76 (39.6%) were positive for E. coli. Smaller notes (R10) recorded the highest E. coli counts per note. Of the 92 notes analyzed for potentially pathogenic bacteria and fungi (second sampling round), 76 (82%) showed growth on at least one of the six culture media used. Sequencing revealed three bacterial (Bacillus, Staphylococcus and Corynebacterium) and two fungal (Clavispora and Rhodotorula) genera. SEM revealed that microorganisms could enter cracks of creased notes. Conclusion: Unlike previous studies conducted where recent contamination could occur, the current study shows that microorganisms can survive on money; samples were collected from a church, where little or no exchange takes place. Moreover, using SEM demonstrates that aged and creased notes favor attachment of bacteria to money and could be of public health concern by transmitting disease within a given population.